2018
DOI: 10.1177/0961203318815764
|View full text |Cite
|
Sign up to set email alerts
|

Complete urological evaluation including sperm DNA fragmentation in male systemic lupus erythematosus patients

Abstract: Objective To evaluate sperm DNA fragmentation analysis in non-azoospermic male systemic lupus erythematosus (SLE) patients. Methods Twenty-eight consecutive male SLE patients (American College of Rheumatology criteria) and 34 healthy controls were evaluated for demographic/exposures data, urological evaluation, hormone profile and sperm analysis (including sperm DNA fragmentation). Clinical features, disease activity/damage scores and treatment were also evaluated. Results The median age (33 (20–52) vs. 36.5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…However, higher sperm DNA fragmentation rate was observed. In contrast to these findings, Tiseo et al (2019) 51 found no correlation between sperm DNA damage and cumulative doses of MMF in male SLE patients.…”
Section: Resultsmentioning
confidence: 83%
“…However, higher sperm DNA fragmentation rate was observed. In contrast to these findings, Tiseo et al (2019) 51 found no correlation between sperm DNA damage and cumulative doses of MMF in male SLE patients.…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, several studies reported lower semen quality in patients treated with cyclophosphamide (CYC) 23‐25 . However, Tiseo et al did not observe any difference in semen parameters of SLE patients and those treated with CYC, but did report a significant increase in sperm DNA fragmentation 26 . Although there is some suggestion FSH may be increased in these patients, primary hypogonadism was not common in SLE or CYC treatment.…”
Section: Resultsmentioning
confidence: 98%
“…However, in the literature, there appears to be no guideline to suggest the optimum period of abstinence in relation to semen parameters and DNA fragmentation level for patients with SLE or in those who have had prior exposure to gonadotoxic treatment. A very recent study by Tiseo et al [31] revealed the DNA fragmentation level to be significantly higher in nonazoospermic patients with SLE when compared with a non-SLE control group. However, the period of abstinence in this study was not mentioned.…”
Section: Discussionmentioning
confidence: 96%